Representation of plastic and cosmetic surgeons in British newspapers. Issue 8 (August 2022) - Goodarzi, M.R.; Breakey, R.W.F.; Jones, A.P.; Allison, K.P.
Summary: Background: The aim of this study was to investigate the use of the terms "plastic surgeon" or "cosmetic surgeon" in British newspapers. Methods: Based on readership volume, the top eight British newspapers were searched for articles written between 09/2016-09/2021 for their use of keywords "plastic surgeon" OR "cosmetic surgeon". The names of the doctors referenced were searched in the GMC register to determine their speciality registration. Results: A total of 2326 articles were read. 2107 (91%) articles were excluded as they did not refer to a specifically named doctor. Of the 219 articles remaining, 136 referenced "plastic surgeons". 22 (16%) doctors referred to as "plastic surgeons" were not on the GMC speciality register for plastic surgery. 83 articles made reference to "cosmetic surgeons". 39 (47%) were on the plastic surgery register but 11 (13%) were on other higher surgical registers [ENT (2) and ophthalmology (9)]. 18 (22%) cosmetic surgeons were registered as GPs and 15 (18%) were not on any speciality register. Discussion: There is mis-representation of individuals performing cosmetic procedures as plastic surgeons regardless of their speciality or training. This prevents public awareness of the true scope of plastic and reconstructive surgery as a speciality in its own right.